Propagation of Love Waves in Composite Layered Structures Loaded with Viscous Liquid. (2016) - Pramanik, Abhijit; Gupta, Shishir
Abstract: This article describes the theory of Love wave propagation in a layered elastic structure loaded on its surface by a viscous (Newtonian) liquid. The layered elastic structure consists of a composite layer lying over an inhomogeneous half space. The method of separation of variables has been used to obtain the frequency equation with suitable boundary conditions. An analytical expression for the complex dispersion equation of Love waves has been established. The influence of the viscosity of liquid, inhomogeneity on the dispersion curves of phase velocity of the Love wave amplitude is analysed graphically.